Bouncing back from psychological contract breach: How commitment recovers over time. (18th August 2015) - Solinger, Omar N.; Hofmans, Joeri; Bal, P. Matthijs; Jansen, Paul G. W.
Summary: The post‐violation model of the psychological contract outlines four ways in which a psychological contract may be resolved after breach (i.e., psychological contract thriving, reactivation, impairment, and dissolution). To explore the implications of this model for post‐breach restoration of organizational commitment, we recorded dynamic patterns of organizational commitment across a fine‐grained longitudinal design in a sample of young academics who reported breach events while undergoing job changes ( N = 109). By tracking organizational commitment up until 10 weeks after the first reported breach event, we ascertain that employees may indeed bounce back from a breach incidence, albeit that some employees do so more successfully than others. We further demonstrate that the emotional impact of the breach and post‐breach perceived organizational support are related to the success of the breach resolution process. Additionally, we reveal a nonlinear component in post‐breach trajectories of commitment that suggests that processes determining breach resolution success are more complex than currently assumed. Copyright © 2015 John Wiley & Sons, Ltd.